Implementasi Marketing Mix pada Objek Wisata Dira Park Ambulu dalam Menciptakan Pengelolaan Berkelanjutan: (Studi Kasus : Dira Park Ambulu) - Agung Sulistyo; Suhartapa Suhartapa; Alif Wibowo (Tourism Scientific Journal, 2022)
Tourism is an important contributor to the regional economy. This condition confirms that tourism needs to be well prepared. The presence of the COVID-19 pandemic has had an impact on all sectors, including tourism. This situation is characterized by a decrease in the number of tourist visits, both local and foreign. Another impact of the pandemic is the lack of management focus on managing tourist attractions. These conditions directly affect the implementation of marketing strategies in achieving management targets. The purpose of this study is to analyze the application of the 7p marketing mix to the tourist attraction of Dira Park Ambulu in creating sustainable creative tourism. A qualitative design is used in this study, which explores everything about managing tourist attractions. Data collection through interviews combined with the 7p marketing mix instrument. The selected informants came from management, employees, and visitors who were enjoying Dira Park Ambulu's services. The Miles Huberman method is used in data processing and analysis through the stages of transcription, reduction, coding, categorization, and drawing conclusions. The study's findings show what would happen if Dira Park Ambulu's tourist attraction did not meet the 7-point marketing mix concept. Some of the instruments used in the 7p marketing mix instrument, including products, prices, marketing distribution channels, promotions, human resources, processes, and physical evidence, have not been fully implemented. The results of this study confirm that the management of the Dira Park Ambulu tourist attraction needs to thoroughly implement the 7p marketing mix instrument.